2021
DOI: 10.5217/ir.2020.00013
|View full text |Cite
|
Sign up to set email alerts
|

Long-term safety and effectiveness of adalimumab in 462 patients with intestinal Behçet’s disease: results from a large real-world observational study

Abstract: Mediterranean basin, corresponding to the Old Silk Road, an ancient trading route stretching between the Mediterranean, the Middle East, and the Far East 3 with an estimated prevalence of 13.5-20 cases per 100,000 people in Japan, Korea, China, Iran, and Saudi Arabia. 2 In Japan, the estimated prevalence of BD was reported as 14.9 per 100,000 people in 2002. 4 According to the diagnostic criteria published by the Japanese Ministry of Health, Labour and Welfare, 5,6 the major symptoms of BD include recurrent or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 36 publications
2
28
2
Order By: Relevance
“…9 Previous studies have shown that anti-TNF agents, including infliximab and adalimumab, led to the relief of gastrointestinal symptoms and ulcers in gastrointestinal tract in patients with Behcet's disease. [15][16][17][27][28][29][30][31][32][33][34][35][36] However, these studies were single-arm cohort studies. No randomized clinical trials have been conducted in this field.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Previous studies have shown that anti-TNF agents, including infliximab and adalimumab, led to the relief of gastrointestinal symptoms and ulcers in gastrointestinal tract in patients with Behcet's disease. [15][16][17][27][28][29][30][31][32][33][34][35][36] However, these studies were single-arm cohort studies. No randomized clinical trials have been conducted in this field.…”
Section: Discussionmentioning
confidence: 99%
“…Gastrointestinal involvement was considered more dangerous to patients with Behcet's disease, as the prognosis was usually worse 9 . Previous studies have shown that anti‐TNF agents, including infliximab and adalimumab, led to the relief of gastrointestinal symptoms and ulcers in gastrointestinal tract in patients with Behcet's disease 15–17,27–36 . However, these studies were single‐arm cohort studies.…”
Section: Discussionmentioning
confidence: 99%
“…One patient who was treated for pre-existing chronic myelomonocytic leukemia experienced relapse thereof during the follow-up period. 24 Meanwhile, the safety of anti-TNF-α therapy in ulcerative colitis has been evaluated in 2088 patients, and a frequency of serious side effects of 16.9% was reported. 38 Despite a lower frequency of SAEs was indicated in our study, further research is needed to explore the feasibility of anti-TNF-α agents for treatment of intestinal BD.…”
Section: Discussionmentioning
confidence: 99%
“…15 A prospective observational study of 462 Japanese patients with intestinal Behçet's disease treated with adalimumab reported the long-term efficacy and safety of adalimumab. 16 In Japan, anti-TNF-α antibodies available for treating intestinal Behçet's disease include infliximab and adalimumab. Administration of adalimumab at 80 mg every 2 weeks is not approved for patients with intestinal Behçet's disease who insufficiently respond to treatment, unlike in the case of patients with Crohn's disease.…”
Section: Discussionmentioning
confidence: 99%